2009
DOI: 10.1021/ci9000053
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Scoring Functions on a Diverse Test Set

Abstract: Scoring functions are widely applied to the evaluation of protein-ligand binding in structure-based drug design. We have conducted a comparative assessment of 16 popular scoring functions implemented in main-stream commercial software or released by academic research groups. A set of 195 diverse protein-ligand complexes with high-resolution crystal structures and reliable binding constants were selected through a systematic nonredundant sampling of the PDBbind database and used as the primary test set in our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
736
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 468 publications
(754 citation statements)
references
References 89 publications
13
736
1
4
Order By: Relevance
“…It is well known, however, that it is difficult to accurately predict experimental binding affinities using the scoring functions developed for docking programs and, albeit less difficult, to correlate docking scores with experimental binding affinities (56). A strategy for overcoming this limitation, which has been successfully applied to various targets (34 -37, 39), is to rescore the poses using the MM-GBSA method to calculate binding free energies (34).…”
Section: E184amentioning
confidence: 99%
“…It is well known, however, that it is difficult to accurately predict experimental binding affinities using the scoring functions developed for docking programs and, albeit less difficult, to correlate docking scores with experimental binding affinities (56). A strategy for overcoming this limitation, which has been successfully applied to various targets (34 -37, 39), is to rescore the poses using the MM-GBSA method to calculate binding free energies (34).…”
Section: E184amentioning
confidence: 99%
“…The HotLig showed ∼85%-90% success rates for predicting ligand binding poses (12). On the other hand, the X-score was reported to be the best scoring function for ranking protein-ligand affinities while comparing with many other well-known scoring programs (25,26). Fig.…”
Section: Zaa Interacts With the Hydrophobic Pocket Of Md-2 To Block Lmentioning
confidence: 98%
“…To investigate whether ZAA interrupts TLR4 signaling by competing the binding of LPS to MD-2, we applied an in silico molecular docking analysis to simulate the interactions between ZAA and MD-2. Previous studies have shown that knowledgebased scoring functions are better methods for prediction of protein-ligand interactions, whereas empirically based scoring functions are more effective for predicting ligand-binding affinities (25,26). Therefore, we used a new knowledge-based scoring program, HotLig, to predict the molecular interactions between ZAA and MD-2.…”
Section: Zaa Interacts With the Hydrophobic Pocket Of Md-2 To Block Lmentioning
confidence: 99%
“…PDBbind (pdbbind.org.cn and pdbbind.org) [77][78][79] , like BindingMOAD above, collects measured affinities for many types of complexes in the PDB, including protein-small molecule, protein-protein, and nucleic acid-small molecule systems. The current version at pdbbind-org.cn provides about 8,000 data, of which about 6,000 are for protein-small molecule complexes, and is free for academic and commercial use, on acceptance of a license agreement.…”
Section: Other Small Molecule Databases Ofmentioning
confidence: 99%